2016
DOI: 10.1051/0004-6361/201629101
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory rotational ground state transitions of NH3D+and CF+

Abstract: Aims. This paper reports accurate laboratory frequencies of the rotational ground state transitions of two astronomically relevant molecular ions, NH 3 D + and CF + . Methods. Spectra in the millimetre-wave band were recorded by the method of rotational state-selective attachment of He atoms to the molecular ions stored and cooled in a cryogenic ion trap held at 4 K. The lowest rotational transition in the A state (ortho state) of NH 3 D + (J K = 1 0 −0 0 ), and the two hyperfine components of the ground state… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Those molecules that do not show elongations, such as H 2 CNH and NH 2 D, are probably rapidly destroyed after their release in the gas phase. In the case of NH 2 D, the tentative detection of NH 3 D + by Cernicharo et al (2013), later confirmed by laboratory measurements of Stoffels et al (2016), could suggest an explanation. NH 2 D can react with H + 3 to form NH 3 D + in two-thirds of the cases, and NH 4 + + HD in one-third of the cases.…”
Section: Discussionmentioning
confidence: 76%
“…Those molecules that do not show elongations, such as H 2 CNH and NH 2 D, are probably rapidly destroyed after their release in the gas phase. In the case of NH 2 D, the tentative detection of NH 3 D + by Cernicharo et al (2013), later confirmed by laboratory measurements of Stoffels et al (2016), could suggest an explanation. NH 2 D can react with H + 3 to form NH 3 D + in two-thirds of the cases, and NH 4 + + HD in one-third of the cases.…”
Section: Discussionmentioning
confidence: 76%
“…The spectroscopy of CH + was facilitated by a cryogenic ion trap experiment, in which the mentioned parasitic reactants are frozen out. As the applied trapping setup (Asvany et al (2010, 2014)) and the action schemes for rovibrational as well as pure rotational spectroscopy have been thoroughly documented by Asvany et al (2014); Savić et al (2015); Jusko et al (2016, 2017); Doménech et al (2017); Stoffels et al (2016); Brünken et al (2014, 2017), only a brief description is given here. The CH + (similarly 13 CH + and CD + ) ions have been generated in a storage ion source by bombarding the precursor gas (CH 4 Linde 5.5, 13 CH 4 Sigma Aldrich 99%, or CD4 Cambridge Isotope Laboratories 99%, respectively) with electrons (with energies in the range 30-40 eV).…”
Section: Methodsmentioning
confidence: 99%
“…Another scheme is infrared-(sub)mm double resonance LIR, which was applied to CH 2 D + [26], CD 2 H + [27], and OH − [28]. Rotational state-dependent attachment of He atoms to cold molecules has been successfully applied to CD + [29], l-C 3 H + [9], CF + and NH 3 D + [30]. Terahertz-visible two-photon rotational spectroscopy is an alternative method that has been developed in our group to probe rotational transitions of molecular anions and this has been applied to OD − [31].…”
mentioning
confidence: 99%